The role of ultrasound in the diagnosis and management of postpartum hemorrhage. Issue 2 (13th February 2023) - Mappa, Ilenia; Patrizi, Lodovico; Maruotti, Giuseppe Maria; Carbone, Luigi; D'Antonio, Francesco; Rizzo, Giuseppe
Abstract: Postpartum hemorrhage (PPH) is the leading cause of death or severe morbidity for the mother after delivery. As a consequence healthcare staff working in the delivery room should be trained to perform a prompt diagnosis and adequate management of PPH. Uneventful outcome is induced correct identification of the underlying cause of hemorrhage. Ultrasound is a promising technique for the prompt diagnosis of PPH etiology. Indeed, it is easily available, with relatively low cost, not using ionizing radiation, and can be used in different settings including the labor room, the operating theater and at the bedside of an affected women. In order to be effective Obstetricians should have an adequate knowledge of postpartum ultrasonography. In this article, we will review the sonographic findings occurring in PPH, in the differential diagnosis of the underlying cause of hemorrhage, that include retained placenta, morbidly adherent placenta, rupture of the uterus uterine, vascular anomalies of the uterine arteries and uterine inversion. We will also provide an algorithm to manage PPH according to the ultrasonographic findings. Abstract : Postpartum hemorrhage is the leading cause of maternal mortality. Its management requires a prompt diagnosis of the underlying cause and a close monitoring of maternal condition. In this review, we will describe the role of ultrasound in managing PPH.